2009
DOI: 10.1002/jbm.b.31497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyaluronic acid sponge as a scaffold on odontoblastic cell line and amputated dental pulp

Abstract: It is important to develop a suitable three-dimensional scaffold for the regeneration therapy of dental pulp. In the present study, the effects of hyaluronic acid (HA) sponge on responses of the odontoblastic cell line (KN-3 cells) in vitro, as well as responses of amputated dental pulp of rat molar in vivo, were examined. In vitro, KN-3 cells adhered to the stable structure of HA sponge and that of collagen sponge. In vivo, dental pulp proliferation and vessel invasion were observed in both sponges implanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…Hyaluronic acid and collagen sponges have shown to induce and sustain dental pulp proliferation and invasion of vessels from amputated dental pulp. Hyaluronic acid sponge induces less inflammatory response compared to collagen sponge [22].…”
Section: Hyaluronic Acidmentioning
confidence: 95%
“…Hyaluronic acid and collagen sponges have shown to induce and sustain dental pulp proliferation and invasion of vessels from amputated dental pulp. Hyaluronic acid sponge induces less inflammatory response compared to collagen sponge [22].…”
Section: Hyaluronic Acidmentioning
confidence: 95%
“…In vivo results, following implantation of both sponges in dentin defect areas, showed that dental pulp proliferation and invasion of vessels into both sponges were well induced from amputated dental pulp, suggesting that HA sponge has an ability to sustain dental pulp tissue regenerated from residual amputated dental pulp. Furthermore, we found that the inflammatory responses of KN-3 cells and the amputated dental pulp to HA sponge were lower than those against collagen sponge, suggesting that HA sponge has biocompatibility and biodegradation characteristics as well as an appropriate structure to make it suitable for dental pulp regeneration [101] (Figure 8). We also examined the effects of HA gel on neuronal differentiation of PC12 pheochromocytoma cells, which respond to nerve growth factor (NGF) by extending neurites and exhibit a variety of properties of adrenal medullary chromaffin cells.…”
Section: Hyaluronic Acid Sponge For Dental Pulpmentioning
confidence: 98%
“…In comparison with the collagen sponge, the hyaluronic acid sponge can support cell growth in culture and in vivo from the amputated dental pulp of rat molars, with fewer immunologic reactions as shown by expression of inflammatory cytokines tumor necrosis factor (TNF)-a and interleukin-6, as well as leukocyte infiltration. [95] However, when used as an injectable hyaluronic acid gel for soft-tissue augmentation, adverse hypersensitivity reactions were reported, due to impurities and bacterial contamination. [96] Fibrin:-Fibrin consists of the blood proteins fibrinogen and thrombin, which are produced naturally in the body after injury to establish hemostasis and enhance wound healing.…”
Section: Naturally Derived Scaffold:-alginate:-mentioning
confidence: 99%